Case Report: Pharmacogenomics in clinical practice - a young male with medication-resistant depression and genetic variations in drug-metabolising enzymes - Beer, Cristina; Semmler, Annalese; Voisey, Joanne (Frontiers in Psychiatry, 2025)
Depression is a complex and heterogeneous mental health disorder affecting an estimated 280 million individuals worldwide. Although various antidepressant medications are available, a significant proportion of patients experience medication-resistant depression. This clinical case report highlights the critical importance of integrating pharmacogenomics into clinical practice, which is still not routinely done in many countries, through the detailed examination of a mid-20s male patient diagnosed with medication-resistant depression. Genetic analysis revealed specific variations in the cytochrome P450 genes, namely CYP2D6, CYP2C19, and CYP1A2, which are crucial for drug metabolism. By investigating the impact of these genetic variations on the patient’s treatment response, we provide evidence-based recommendations for adjusting antidepressant medications based on the individual’s unique pharmacogenomic profile. As demonstrated in the case report, this ultimately results in a positive clinical outcome and would have been advantageous to implement earlier as part of the patient’s management.